Reader's digest select editions : as darkness falls / don't tell a soul / all the colours of darkness / an Irish country village - Parry, Bronwyn; Rosenfelt, David; Robinson, Peter; Taylor, Patrick (Sydney, Reader's digest, 2009)
Summary: The Reader's Digest Select Editions are a series of hardcover fiction anthology books, published bi-monthly and available by subscription, from Reader's Digest. Each volume consists of four or five current bestselling novels selected by Digest editors and abridged (or "condensed") to shorter form to accommodate the anthology format. The Four titles as As darkness falls / Don't tell a soul / All the colours of darkness / An Irish country village
Donated by: Student
Keywords: fiction -- Four fiction story -- child murderer -- suicide -- secret services -- physicians -- country life -- Northern Ireland